Synergistic Effects of Different Endophytic Actinobacteria Combined with Organic Fertilizer on Soil Nutrients and Microbial Diversity in Camellia oleifera - Yinghe Peng; Kunpeng Cui; Huimin Jian; Zhen Zhang; Longsheng Chen; Yanming Xu; Zhigang Li; Hongsheng Liu; Ting Xu; Rui Wang (Microorganisms)
Camellia oleifera, a prominent species of edible oil tree in China, depends on improved soil fertility for its sustainable growth. Although the application of bacterial manure has been demonstrated to enhance soil nutrient conditions, the specific contributions of endophytes within fertilizers and their interactions with soil microbial ecosystems remain inadequately explored. This study investigates the impact of organic fertilizers combined with three endophytes (CoT10, CoH27, and CoH17) on the physicochemical properties, enzymatic activities, and microbial diversity of soils in C. oleifera plantations. Findings indicate that the integration of endophytes with organic fertilizers significantly improved soil nutrient levels (including total nitrogen, total phosphorus, and hydrolysable nitrogen), enzymatic activities (such as phosphatase, amylase, and nitrate reductase), and microbial diversity compared to the application of organic fertilizer alone. Notably, the endophyte CoT10, when applied alone with organic fertilizer, resulted in increased levels of total nitrogen, total phosphorus, and hydrolysable nitrogen in the soil, as well as a marked enhancement in the activities of soil phosphatase, amylase, and nitrate reductase. Furthermore, the combination of CoT10 with other endophytes in organic fertilizer improved the functionality of the other microorganisms and the efficiency of organic fertilizer utilization. This study underscores the synergistic effects of endophytes and organic fertilizers, providing scientific insights and practical strategies for the sustainable cultivation of C. oleifera.